Efficient Distortion Mitigation and Partition Reduction in Mapping Global Geodata: Dual Orthogonal Equidistant Cylindrical Projection Approach - Aleksandar Dimitrijević; Aleksandar Milosavljević; Dejan Rančić (ISPRS International Journal of Geo-Information, 2023)
The rapid growth in Earth’s global geospatial data necessitates an efficient system for organizing the data, facilitating data fusion from diverse sources, and promoting interoperability. Mapping the spheroidal surface of the planet presents significant challenges as it involves balancing distortion and splitting the surface into multiple partitions. The distortion decreases as the number of partitions increases, but, at the same time, the complexity of data processing increases since each partition represents a separate dataset and is defined in its own local coordinate system. In this paper, we propose the Dual Orthogonal Equidistant Cylindrical projection method to mitigate distortion and reduce the number of partitions. Additionally, we use the rotation of the graticule system on the globe to achieve the oblique aspect, which effectively minimizes average angular and areal distortions of Earth’s landmass and reduces the interruption of continental plates caused by partition edges. By incorporating auxiliary latitudes and proposing an approximate authalic latitude, we further enhance the mapping of the ellipsoid onto the sphere, simplifying calculations. The experimental results demonstrate a substantial reduction in distortion and interruption of continental plates. With only two partitions, an average landmass angular distortion of less than 3.56 degrees and an average areal distortion of less than 1.07 were achieved.